North Kalimantan Base Sector Analysis Gross Regional Domestic Product Approach - Dewi Ratna Lestari; Michael Michael; Aji Sofyan Effendi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study is to find out which sectors are the leading sectors in North Kalimantan Province in 2017 – 2021, What economic sectors have fast growth rates in shifting economic sectors in North Kalimantan Province in 2017 – 2021, Which economic sectors have the power strong competitiveness in shifting economic sectors in North Kalimantan Province in 2017 - 2021. What economic sectors are included in the criteria as prime, potential, developing and underdeveloped sectors in North Kalimantan Province in 2017 - 2021. Quantitative analysis methods used in processing this data is Location quotient (LQ), Shift Share, Growth Ratio Model (MRP) and Overlay Analysis processed using Microsoft Office Excel. The results of the study show that the economic sectors which are categorized as basic sectors in North Kalimantan Province in 2017 – 2021 are the Agriculture, Forestry and Fisheries sectors; Mining and excavation; Construction; Transportation and Warehousing; Administration of Government, Defense and mandatory social security; Education Services.